Associations between sleep disorders, anxiety, depression, and the phases of sarcopenia to severe sarcopenia: findings from the WCHAT study - Xu, Zhigang; Ma, Ya; Ning, Huang; Jia, Shuli; Zhang, Gongchang; Xia, Xin; Hu, Fengjuan; Ge, Meiling; Liu, Xiaolei; Dong, Birong (Frontiers in Public Health, 2025)
BackgroundSarcopenia not only leads to impaired physical function but also may be associated with changes in sleep and mental health as individuals age. Research on the relationships between sleep disorders, anxiety, and depression and adult-onset sarcopenia is limited, however, with no reports of the associations between them and different severity of sarcopenia. The objective of this research endeavor is to investigate the associations between sarcopenia and sleep disturbances, anxiety, as well as depression, within a multi-ethnic population in western China.MethodWe conducted a cross-sectional study consisting of 4,500 participants from the WCHAT study. The diagnostic method recommended by the Asian Working Group for Sarcopenia in 2019 was used to screen for sarcopenia. The Pittsburgh Sleep Quality Index (PSQI), the 7-item Generalized Anxiety Disorder Questionnaire (GAD-7), and the 15-item Geriatric Depression Scale (GDS-15) were used to assess sleep quality, anxiety, and depression, respectively. The relationships among sleep, anxiety, depression, and the different sarcopenia subgroups were evaluated by using multivariate regression models. In addition, subgroup of gender analysis were performed.ResultsAmong the 4,500 participants surveyed in the western region of China, 408 (9.06%) were diagnosed with sarcopenia and 618 (13.73%) with severe sarcopenia. A total of 2,515 individuals (55.88%) had poor sleep quality, while 842 (18.71%) suffered from anxiety, and 1,045 (23.22%) had depression. Good sleeping quality were negatively associated with severe sarcopenia (OR: 0.80, 95%CI 0.66–0.97) in model 1, whereas depression was positively associated with severe sarcopenia in three models (model 1: OR: 1.39, 95%CI 1.13–1.71; model 2: OR: 1.46, 95%CI 1.16–1.85; model 3: OR: 1.43, 95%CI 1.13–1.81). However, anxiety status was not associated with sarcopenia in our study.ConclusionIt was found that good sleep quality were negatively associated with severe sarcopenia, and depression was positively associated with severe sarcopenia. These findings suggested that early intervention in sleep quality and depression may be one of the effective strategies to delay or reduce the severity of sarcopenia.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR1800018895.